Perancangan Perancangan Aplikasi Cari Kerja Berbasis Website Menggunakan Laravel - Bagas Yusuf Faqih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The development of information and communication technology is growing rapidly. Especially when it comes to information, information plays a major role in life. In this modern era information is supported by one of the technologies called the internet. In this case the internet provides easy to display information about job openings, one of which is the job website. Without information it would be very difficult to get something in the want, such as getting a job. Work is very important for the survival of some people therefore many people who have difficulty in obtaining information on a job, but there are also people who have a company that also has difficulty getting employees quickly and with skills that suit the required fields. To solve the problem, a web-based job application design called a job search website, using the waterfall method, was created using php programming language and MySQL as a database. With this application is expected to facilitate applicants in finding information about job openings and facilitate a company that is in need of employees quickly and with the right skills.